MolekulAR: A conceptual design of interactive chemistry learning based on augmented reality to improve science literacy - Febiola Irashai Siti Mawla Yuri (Journal of Environment and Geography Education, 2025)
Background: Chemistry education in Indonesia faces persistent challenges in improving science literacy due to the abstract nature of chemical concepts and limited access to interactive, effective learning tools. Augmented Reality (AR) technology offers a promising approach by providing immersive, visual learning experiences that facilitate comprehension of complex topics such as molecular structures and chemical reactions. Methods: This study designs and develops MolekulAR, an AR-based interactive chemistry learning application aligned with the national curriculum. The development process incorporates a Pentahelix collaboration model involving educators, government, industry, communities, and media to ensure pedagogical relevance and technical feasibility. The application integrates interactive 3D molecular models, real-time reaction simulations, and customized learning modules. Evaluation was conducted through expert validation, classroom trials, and user feedback. Findings: Results demonstrate that MolekulAR significantly improves student motivation, engagement, and conceptual understanding of challenging chemistry subjects. Features including Scan to Structure, Lab Simulation, and Explore Molecules enable hands-on, exploratory learning, making abstract content more tangible. The study also identifies barriers such as technological infrastructure limitations, unequal device accessibility, and teacher readiness. Conclusion: MolekulAR represents a scalable and sustainable educational tool that aligns AR technology with curriculum goals and addresses pedagogical and infrastructural challenges, fostering improved science literacy across Indonesian classrooms. Sustained cross-sector collaboration is essential for effective implementation. Novelty/Originality of this article: This research uniquely combines AR technology, curriculum alignment, and a systemic multi-stakeholder (Pentahelix) collaboration model to deliver an innovative and contextually relevant solution that advances interactive chemistry learning and science literacy in Indonesia.